2013
DOI: 10.1007/s12253-013-9724-z
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin Disease Therapy Induced Second Malignancy Susceptibility 6q21 Functional Variants in Roma and Hungarian Population Samples

Abstract: Patients treated successfully for pediatric Hodgkin's lymphoma are known to develop secondary malignancies; care is already taken in treatment to prevent this adverse effect. Recent GWAS study identified rs4946728 and rs1040411 noncoding SNPs located between PRDM1 and ATG1 genes on chromosome 6q21 as risk factors for secondary malignancies in patients formerly treated with radiotherapy for pediatric Hodgkin disease. We investigated the allele frequencies of these two SNPs in biobanked, randomly selected DNA of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Two independent genome wide association studies (GWAS) reported that variants at chromosome 6q21 in pediatric HL patients were associated with radiation induced second malignant neoplasms (SMNs) [89, 90]. Best and colleagues revealed significant associations between SNPs on chromosome 6q21, rs4946728 ( P = 0.002), and rs1040411 ( P = 0.03) and the odds of developing SMNs, which increased by >3-fold and >2-fold per copy of the major allele rs4946728 and rs1040411, respectively [89].…”
Section: Molecular and Genetic Prognostic Biomarkersmentioning
confidence: 99%
“…Two independent genome wide association studies (GWAS) reported that variants at chromosome 6q21 in pediatric HL patients were associated with radiation induced second malignant neoplasms (SMNs) [89, 90]. Best and colleagues revealed significant associations between SNPs on chromosome 6q21, rs4946728 ( P = 0.002), and rs1040411 ( P = 0.03) and the odds of developing SMNs, which increased by >3-fold and >2-fold per copy of the major allele rs4946728 and rs1040411, respectively [89].…”
Section: Molecular and Genetic Prognostic Biomarkersmentioning
confidence: 99%
“…[6][7][8] Best et al showed 2 variants at chromosome 6q21 to be associated with subsequent malignant neoplasm in survivors of HL treated with radiation therapy as children but not as adults. 6 Ma et al showed that genetic variation in FGFR2 influences breast cancer risk in HL patients treated with radiotherapy.…”
Section: Second Malignancymentioning
confidence: 99%
“…Recently, genome-wide association studies (GWAS) have identified rs4946728 and rs1040411 non-coding single nucleotide polymorphisms (SNPs) located on chromosome 6q21 as a risk factor for RISM in pediatric HL. Varszegi et al [ 9 ] investigated the frequencies of the two SNPs (those identified in GWAS study) in healthy Hungarians and Romanians. The percentage of these SNPs was higher than those observed in controls and are in the range of the cases of the original GWAS study.…”
Section: Pathogenesismentioning
confidence: 99%